2018
DOI: 10.1111/jocn.14560
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnoea and self‐management strategies in patients admitted to the emergency department: A study of patients’ experiences

Abstract: It would be relevant to further investigate whether prehospital interventions may remedy acute dyspnoea among chronically ill patients, and whether such interventions are cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The experiences of breathlessness, the strategies around managing the situation and the awareness of when it was necessary to call for help were different for the patients in this study. This is consistent with other authors (Hutchinson et al, 2020;Karasouli et al, 2016;Larsen et al, 2018), who found that it was difficult for patients to know when their condition was serious enough to require medical attention. Some people who had previous experience with breathlessness (Karasouli et al, 2016;Larsen et al, 2018) found it easier to determine when this was necessary, while others (Karasouli et al, 2016) tried to avoid going to the hospital as long as possible, despite their deteriorating clinical situation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The experiences of breathlessness, the strategies around managing the situation and the awareness of when it was necessary to call for help were different for the patients in this study. This is consistent with other authors (Hutchinson et al, 2020;Karasouli et al, 2016;Larsen et al, 2018), who found that it was difficult for patients to know when their condition was serious enough to require medical attention. Some people who had previous experience with breathlessness (Karasouli et al, 2016;Larsen et al, 2018) found it easier to determine when this was necessary, while others (Karasouli et al, 2016) tried to avoid going to the hospital as long as possible, despite their deteriorating clinical situation.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with other authors (Hutchinson et al, 2020;Karasouli et al, 2016;Larsen et al, 2018), who found that it was difficult for patients to know when their condition was serious enough to require medical attention. Some people who had previous experience with breathlessness (Karasouli et al, 2016;Larsen et al, 2018) found it easier to determine when this was necessary, while others (Karasouli et al, 2016) tried to avoid going to the hospital as long as possible, despite their deteriorating clinical situation. In the latter study, none of the patients wanted to be admitted to the hospital, but they were eventually forced to accept the situation because all other options had been exhausted.…”
Section: Discussionsupporting
confidence: 92%
“…As a COA, functioning has been used in several health fields, e.g. in the health care of people with schizophrenia 8 ; migraine 9 ; cancer 10 ; arthrogryposis 11 ; dyspnea 12 ; stroke 13 ; chronic musculoskeletal pain 14 ; congenital heart disease 15 ; and prior to hematopoietic stem cell transplantation 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A Danish study, which conducted interviews 2 weeks after the patients had contacted the Emergency department due to dyspnea, found that patients, regardless of familiarity with dyspnea, worked out self-management strategies and stayed home for as long as possible, seemingly postponing seeking medical care [ 24 ]. Another qualitative study exploring the experience of patients with advanced COPD after a life-threatening event found that participants expressed confidence in the hospital to reduce their physical symptoms and related anxiety.…”
Section: Discussionmentioning
confidence: 99%